Soil macrofauna and soil quality in agricultural and livestock agroecosystems of Campeche - Castillo-Trejo, Eric Yanuario; Flota-Bañuelos, Carolina; Alcudia-Pérez, Julia; Fraire-Cordero, Silvia; Rosales-Martínez, Verónica; Quej-Chí, Víctor Hugo (Revista Mexicana de Ciencias Agrícolas, 2023)
Crops in the state of Campeche are intensifying, this causes transformations in the physicochemical and biological properties of the soil. The objective was to determine the effect of agroecosystems on soil macrofauna and soil properties. Ten sampling points per agroecosystem were taken, with three repetitions each. The sites were chosen according to the agricultural use (grassland, forest, intensive and traditional agricultural) and time of use (≥8 years). One kilogram from each sample was taken at a depth of 20 cm, then placed in polyethylene bags. The pH, electrical conductivity, organic matter, available phosphorus, total nitrogen and soil macrofauna were determined. With the data of each variable, an analysis of variance was performed and to determine the differences between land uses and sites, a mean test was carried out according to the Tukey statistic (p≤ 0.05), using the software Statistica version 7.1. The grassland agroecosystem of Palizada presented the best characteristics in the soils, with pH of 7.29, P, OM, N of 1.31 mg kg-1, 5.05% and 0.31%, respectively and soil fauna with 66 individuals. The agroecosystem with the lowest soil quality was intensive crops of Hopelchén, with moderately acidic pHs (6.44), higher amount of P (33.42 mg kg-1), lower OM (2.59%) and high N contents (0.23%) and without soil macrofauna. Soil management in agricultural agroecosystems does not favor the presence of soil macrofauna nor does it maintain the nutrients necessary for the proper functioning and quality of the soil.
Keywords: macroinvertebrates; production systems; soil quality